A transversalidade da experiência estética na educação infantil - Bahiense, Adriana Andrade (2015)
This research intends to talk about the questions about The Transversality of the aesthetic experience in early childhood education. The first part of the research dialogs about the child s age and its development stages, the relation of aesthetics and art in childhood education, an attempt of reflection on childhood education and artistic experience as tools for human and complex learning. The second part of the research deals with the aesthetic experience within the theories of complexity, the artistic, human and cultural relations which are built within social life and in artistic experience. It works with the epistemology and religiosity, aspects that are dialoguing between themselves about the aesthetic experience and the meaning of making and creating, a quest for the general within the personal area. And the third and last part of the research presents actions promoted within the aesthetic experience in child development, art-play tools to read the child s world. It is a quest for a pedagogical tool which can provide the concept and meaning for transversality of art in education, artistic proposals, art-play for childhood education.